Pengaruh pelatihan dan kompetensi karyawan terhadap kinerja karyawan dengan kepuasan kerja sebagai variabel intervening pada PT. Warisbama Emeste - Putri Rahmawati (Cerdika: Jurnal Ilmiah Indonesia, 2025)
This study aims to determine the effect of employee training and competency on employee performance with job satisfaction as an intervening variable in PT. Warisbama Emeste. The method of collecting data is through surveys and distributing questionnaires to employees as respondents using a quantitative approach. The data analysis technique used is structural Equation Modeling (SEM) analysis with Partial Least Square (PLS) 3.0. The results of the study show that training has a positive and significant effect on job satisfaction at PT. Warisbama Emeste. Employee competence has a positive and significant effect on job satisfaction at PT. Warisbama Emeste. Training has a positive and insignificant effect on employee performance at PT. Warisbama Emeste. Employee competence has a positive and insignificant effect on employee performance at PT. Warisbama Emeste. Job satisfaction has a positive and significant effect on employee performance at PT. Warisbama Emeste. Training has a positive and insignificant effect on employee performance with job satisfaction as an intervening variable at PT. Warisbama Emeste. Employee competence has a positive and insignificant effect on employee performance with job satisfaction as an intervening variable in PT. Warisbama Emeste.